EFEKTIVITAS PENERAPAN METODE MENGHAFAL AL-QUR’AN TERHADAP KEMAMPUAN HAFALAN SANTRI DI PONDOK PESANTREN AL-IMAM ASHIM MAKASSAR - Saprin,; Yahya, Muhammad; Syarif, Ahmad (Istiqra: jurnal hasil penelitian, 2022)
This research discusses the effectiveness of implementing the method of memorizing the Koran on the memorization abilities of students at the Al-Imam Ashim Islamic Boarding School Makassar. Behavioristic theory views learning as a process of changing behavior as a result of the interaction between stimulus and response, and the method is one of the stimuli from teachers that can be applied for learning to memorize the Koran at the Al-Imam Ashim Islamic boarding school. This type of research is quantitative research. The population in this study were all students at the Al-Imam Ashim Islamic Boarding School in Makassar with a total of 460 people, a sample of 48 students. the application of the method of memorizing the Qur'an through learning tahfiz} al-Qur'an is effective on the memorization ability of students at the Al-Imam Ashim Islamic Boarding School Makassar